Students’ Difficulties in Understanding Arabic in the Modern Learning Era: Evidence from Generation Z - Desti Ana Ananda Kusuma; Muthoifin (Walidem Institute and Publishing (WIP), 2025)
Objective: This research aims to find out and analyze various difficulties experienced by students in the process of learning Arabic at school. Arabic is one of the subjects that requires the ability to understand vocabulary, grammar, reading, writing, listening, and speaking skills. Theoretical framework: The theoretical framework of this learning environment is that there are internal factors, including learning motivation, interests, basic abilities, and mastery of Arabic vocabulary (mufradat). Students who have low motivation tend to be less active in participating in learning, so they have difficulty understanding the material. Literature review: This review examines that previous studies show that Arabic language learning still faces various obstacles that affect students' understanding of the material. Previous research explained that low mastery of mufradat, lack of motivation to learn, and difficulty understanding the rules of nahwu are the main factors that hinder learning Arabic. Method: This study uses a qualitative method with a descriptive approach to analyze students' difficulties in understanding Arabic lessons. Results: This study shows that students experience various difficulties in understanding Arabic lessons, both from linguistic aspects and learning factors. The most dominant difficulty is the low mastery of mufradat, so that it is difficult for students to understand the meaning of words and the content of the material studied. Implications: This study shows that students' difficulties are not only caused by low mastery of Arabic vocabulary and rules, but also influenced by less interesting learning methods and a lack of practice of Arabic in daily life. Novelty: This research is expected to make a new contribution to the development of Arabic learning strategies that are more effective, interactive, and in accordance with the needs of students so that the learning process becomes easier to understand and is able to increase students' learning motivation optimally.